2017
DOI: 10.1016/j.jaci.2016.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal B-cell maturation in the bone marrow of patients with germline mutations in PIK3CD

Abstract: Capsule summary Patients with germline mutations in PIK3CD, immunodeficiency, lymphoproliferation, and autoimmunity show a distinct pattern of abnormal B-cell maturation in the bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 9 publications
4
40
0
Order By: Relevance
“…PBMCs were isolated from healthy anonymous blood donors obtained from the Australian Red Cross Service and patients with PIK3CD GOF mutations (Table I). 19,23,24 Viral infection history of healthy donors was unknown. Whole blood was collected from Australian-based patients and sent immediately to the Garvan Institute of Medical Research.…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…PBMCs were isolated from healthy anonymous blood donors obtained from the Australian Red Cross Service and patients with PIK3CD GOF mutations (Table I). 19,23,24 Viral infection history of healthy donors was unknown. Whole blood was collected from Australian-based patients and sent immediately to the Garvan Institute of Medical Research.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…19,31 The other mutations identified in patients in this study (ie, G124D, N334K, E525K, and E1025G) have been reported previously and confirmed to be GOF mutations. 19,23,24 Patients' ages ranged from 4.5 to 67 years (mean, 20.1 years), with patients originating from a variety of ethnicities (Table I). As control subjects, we analyzed PBMCs from 38 healthy donors whose ages ranged from 10 to 71 years (mean, 38.0 years).…”
Section: Patients With Pik3cd Gof Mutations Present With Features Of mentioning
confidence: 99%
“…Patients exhibit a paucity of naïve peripheral blood T cells with a large fraction of T cells displaying activation markers. In contrast, B‐cell development is partially blocked, with increased transitional and few circulating memory B cells . Recurrent respiratory infections are the most common feature of APDS.…”
Section: Activated Pi3k‐delta Syndromementioning
confidence: 99%
“…It highlights that mutations occurring in different parts of the gene can lead to the very same consequences, and should thus be screened in patients with a phenotype resembling APDS. Jean-Marc Plaza, 4 Mélanie Parisot, 5 Benoit Dumont, 6 Delphine Turpin, 7 Etienne Merlin, 8 Despina Moshous, 1,2,9 Nathalie Aladjidi, 10 Bénédicte Neven, 1,2,9 Capucine Picard, 1,2,3 Marina Cavazzana, 1,2,11 Alain Fischer, 1,2,9,12 Anne Durandy, 1,2 Jean-Louis Stephan 6 and Sven Kracker …”
Section: 13mentioning
confidence: 99%